The fully plastic behaviour of monosymmetric steel sections. (15th December 2015) - Kamtekar, A.G.
Highlights: The fully plastic behaviour of monosymmetric steel sections is considered. Interaction between the applied axial force and bending moment is studied. Conditions to be satisfied by interaction curves are defined. A procedure for obtaining interaction curves is given. Anomalies in some interaction curves for T -sections are discussed and explained. Abstract: The behaviour of monosymmetric steel sections when they become fully plastic under the action of an axial force P and a bending moment M applied in the plane of symmetry is considered. Attention is focused on the cross sectional strength, the possibility of local buckling occurring being ignored. The interaction curve that relates the co-existing values of P and M when the section becomes fully plastic is derived. The conditions that this curve must satisfy are established and a procedure for obtaining the curve is given. Interaction curves available for some T -sections are discussed; some anomalies are found in these curves. These are investigated and it is found that they exist because of the procedure used to obtain these curves; they disappear when the procedure proposed in this paper is used instead. If the procedure used previously in the analysis of monosymmetric sections is used to analyse eccentrically loaded doubly symmetric sections, the same anomalies are encountered; these also disappear when the proposed procedure is used.